2022
DOI: 10.1186/s12891-022-05048-8
|View full text |Cite
|
Sign up to set email alerts
|

The comparison of dexamethasone and triamcinolone periarticular administration in total knee arthroplasty: retrospective cohort study

Abstract: Background Intraoperative periarticular injection of corticosteroid effectively reduces perioperative pain in total knee arthroplasty (TKA). However, which corticosteroid is most effective for intraoperative periarticular injection remains controversial. We compared the effects of corticosteroids between dexamethasone and triamcinolone acetonide periarticular administration for reducing pain and postoperative nausea and increasing fasting blood glucose concentrations during the perioperative pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…In addition, referring to the concern of hyperglycemia caused by the administration of corticosteroids, previous studies indicated that the fasting blood glucose of patients treated with topical and intravenous glucocorticoid was significantly increased after TKA [ 52 , 97 , 98 ], which was similar to significant elevation of blood glucose in the glucocorticoid group on POD1 in the study. Hyperglycemia, especially when levels exceed 200 mg/dl has been associated with an increased risk of surgical site infection and wound complications [ 99 , 100 ].…”
Section: Discussionsupporting
confidence: 59%
“…In addition, referring to the concern of hyperglycemia caused by the administration of corticosteroids, previous studies indicated that the fasting blood glucose of patients treated with topical and intravenous glucocorticoid was significantly increased after TKA [ 52 , 97 , 98 ], which was similar to significant elevation of blood glucose in the glucocorticoid group on POD1 in the study. Hyperglycemia, especially when levels exceed 200 mg/dl has been associated with an increased risk of surgical site infection and wound complications [ 99 , 100 ].…”
Section: Discussionsupporting
confidence: 59%
“…Triamcinolone is a long-acting steroid conducted in chronic pain as a local injection. Due to its antiinflammatory properties, it is helpful in controlling pain after ophthalmic and orthopedic surgeries (8). Moreover, its local use in tonsillectomy is effective in head and neck surgery (9).…”
Section: Introductionmentioning
confidence: 99%